2003
DOI: 10.5650/jos.52.73
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calcium Present in Fabric and in Washing Liquor on Detergency.

Abstract: Measurement of the amount of calcium present in cotton fabrics, evaluation of the individual calcium contents in the actual washing liquors for the several washing conditions and several detergency tests were conducted, to clarify how calcium existing not only in water used for washing but also in cotton fabrics to be washed does affect on detergency. Calcium content in cotton fabrics was found to range from 80 to 600mg/g fabrics. When the water hardness is low, the ratio of the calcium content in the fabrics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The resulting high-pH and -alkalinity conditions require acidification prior to discharge, resulting in even greater TDS. Meanwhile, Ca 2þ and Mg 2þ (primary hardness components) can have adverse effects during textile production, such as scaling and chemical interference, and are usually removed from process waters prior to use [15,16]. In addition, lowhardness effluents are typical of regions such as the southeastern United States, where many ground waters and surface waters are naturally low in Ca 2þ and Mg 2þ [11,17].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting high-pH and -alkalinity conditions require acidification prior to discharge, resulting in even greater TDS. Meanwhile, Ca 2þ and Mg 2þ (primary hardness components) can have adverse effects during textile production, such as scaling and chemical interference, and are usually removed from process waters prior to use [15,16]. In addition, lowhardness effluents are typical of regions such as the southeastern United States, where many ground waters and surface waters are naturally low in Ca 2þ and Mg 2þ [11,17].…”
Section: Introductionmentioning
confidence: 99%
“…A small peak of Ca 2p was observed even after washing in the absence of hardness salts. This calcium content may originate from the original cotton fabric 11,12 . However, no peak of Ca 2p was observed in the XPS spectra for used cotton fabrics, which had been cleaned in boiling water twice.…”
Section: Residue On Cotton Ber Surface After Washingmentioning
confidence: 99%
“…They also reported that detergency performance in the presence of magnesium is significantly higher than with calcium 10 . Goto-Doshida et al studied the relation between detergency and calcium on the cotton fabric, or in the wash bath, in the presence of anionic surfactants, nonionic surfactants, and builders 11,12 . They found that the calcium content in cotton fabrics had no influence on detergency at high water hardness, and a negative influence at lower water hardness.…”
Section: Introductionmentioning
confidence: 99%
“…Detergency effectiveness is dependent on many factors, such as the physical properties of the soil, the washing solution and fabrics (substrates), the washing time, temperature, and electrolyte level [1][2][3]. Water hardness, which results from the presence of the divalent cations calcium and magnesium, is considered to be an important factor affecting detergency performance [4][5][6][7][8]. Water hardness is measured in grains per gallon (gpg) or parts per million (ppm).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, washing with hard water can damage the fabric, shortening its life span. It has been found that calcium is retained in the fabric matrix when hard water is used in laundering [4]. Moreover, the residual calcium in the fabric results in making the fabric harsher, stiffer, and more brittle, leading to increased friction and wear as the fabric flexes.…”
Section: Introductionmentioning
confidence: 99%